Extracting Data Elements from Punjabi Language Query - Singh, Harjit; Oberoi, Ashish (International Journal of Computer Sciences and Engineering, 2018)
Databases act as repository of data for various applications. In today‟s scenario every organization has the database to store data and database management systems to access that data. SQL (Structured Query Language) is the language of database management system which is a specific language used to write statements against Relational Database Management Systems to retrieve and manipulate data. But the common user asks query in his/her natural language such as Punjabi Language. That natural language query is not understandable to the computer and hence RDBMS cannot process that query. That natural language query can be processed through Natural Language Processing to understand what kind of data the user wants to retrieve. From that natural language query, we need to retrieve data from the database. To automate the process, various data elements need to be extracted from the Punjabi Language query. These data elements include Entity, Attributes, Condition etc. This paper explains the process of extracting Data Elements from the Punjabi Language query.